World War II in 500 photographs - Daspin, Eileen; Solomon, Michael 1966-, editor (New York, NY : Time Home Entertainment, 2014)
Prelude to war -- 1939 : outbreak of war in Europe -- 1940 : war across two continents -- 1941 : war to the East and West -- 1942 : attack and counterattack -- 1943 : the tide of war turns -- 1944 : overwhelming force -- 1945 : the end of the war -- The aftermath.